Antipsychotic and antidepressant prescribing for 704 297 children and young people with and without intellectual disabilities: record linkage study. (January 2021) - Henderson, Angela; Kinnear, Deborah; Fleming, Michael; Stanley, Bethany; Greenlaw, Nicola; Young-Southward, Genevieve; Pell, Jill P.; Cooper, Sally-Ann
Abstract : Background: Psychotropics are overprescribed for adults with intellectual disabilities; there are few studies in children and young people. Aims: To investigate antipsychotic and antidepressant prescribing in children and young people with and without intellectual disabilities, and prescribing trends. Method: Scotland's annual Pupil Census, which identifies pupils with and without intellectual disabilities, was record-linked to the Prescribing Information System. Antidepressant and antipsychotic data were extracted. Logistic regression was used to analyse prescribing between 2010 and 2013. Results: Of the 704 297 pupils, 16 142 (2.29%) had a record of intellectual disabilities. Antipsychotic and antidepressant use increased over time, and was higher in older pupils; antipsychotic use was higher in boys, and antidepressant use was higher in girls. Overall, antipsychotics were prescribed to 281 (1.74%) pupils with intellectual disabilities and 802 (0.12%) without (adjusted odds ratio 16.85, 95% CI 15.29–18.56). The higher use among those with intellectual disabilities fell each year (adjusted odds ratio 20.19 in 2010 v . 14.24 in 2013). Overall, 191 (1.18%) pupils with intellectual disabilities and 4561 (0.66%) without were prescribed antidepressants (adjusted odds ratio 2.28, 95% CI 2.03–2.56). The difference decreased each year (adjusted odds ratio 3.10 in 2010 v . 2.02 in 2013). Conclusions: Significantly more pupils with intellectual disabilities are prescribed antipsychotics and antidepressants than are other pupils. Prescribing overall increased over time, but less so for pupils with intellectual disabilities; either they are not receiving the same treatment advances as other pupils, or possible overprescribing in the past is changing. More longitudinal data are required.